Effects of long‐term azithromycin therapy on airway oxidative stress markers in non‐cystic fibrosis bronchiectasis. Issue 7 (23rd September 2013) - Diego, Afredo De; Milara, Javier; Martinez‐Moragón, Eva; Palop, Marta; León, Montse; Cortijo, Julio
Abstract: Background and objective: To explore the effect of long‐term therapy with azithromycin in regards to airway oxidative stress markers in exhaled breath condensate (EBC) of adult patients with stable non‐cystic fibrosis (CF) bronchiectasis. Methods: Open‐label prospective study of 30 patients randomized to azithromycin 250 mg three times per week during 3 months (16 patients) or control (14 patients). Primary outcome were changes in nitric oxide, 8‐isoprostane, pH, nitrites and nitrates in EBC. Secondary outcomes were changes in exacerbation rates, dyspnoea (Borg scale), sputum volume (cc), sputum colour (15‐point scale), bacterial infection, health‐related quality of life (St George's Respiratory Questionnaire), lung function and radiological extension. Results: Azithromycin produced a significant decrease in sputum volume (8.9 (1.8) mL vs 2.1 (3.4) mL) and number of exacerbations (0.1 (0.6) vs 1.2 (0.9)). Dyspnoea (0.4 (0.1) vs 0.1 (0.2)) and health‐related quality of life also improved after therapy. However, oxidative stress markers in EBC, systemic inflammatory markers as well as functional respiratory tests did not differ from the control group after therapy. A post‐hoc analysis comparing patients infected or not with Pseudomonas aeruginosa revealed that these effects were more pronounced in infected patients. In this subgroup, treatment was followed by a significant reduction in sputum volume, number of exacerbations, dyspnoea and St George's Respiratory Questionnaire total score. Of all airway oxidative stress markers, only nitrates in EBC were reduced after therapy. Conclusions: Long‐term azythromicin treatment has some clinical benefits in patients with non‐CF stable bronchiectasis, but it does not affect airway oxidative stress markers. Abstract : In patients with bronchiectasis, the mechanism by which macrolides have immune modifying effects independent from their antibacterial activity has not been well established. In this study, we have confirmed azithromycin has some clinical benefits; however, no affect on airway oxidative stress markers was observed. See Editorial, page 1037